The immuno localisation of aplipoproteins B-48 (APO B-48) and B-100 (APO B-100) in human tissues - Mohd Esa, Norhaizan; Nicols, Charlotte; Davies, Michael J.; Gould, Barry J. (2001)
Chylomicron (CM) is lipoprotein, which functions as a carrier of triacylglycerol (TAG) from intestine to the liver. Most of the TAG from CM is removed by the aelion of the lipoprotein lipase. of skeletal muscle and adipose tissue to form CMremnant (CMR). CMR are taken up by the liver and TAG is repackaged in very low density lipoprotein (VLDL) particles, Each CM/CMR and VLDL contains one molecule of apo B-48 and apo B-IOO respectively which remains within the particle until removal from plasma, making it an ideal marker for the metabolism of these two postprandial lipoproteins. The specific antiserum to apo B-48, which recognizes the C-terminal end ofthe protein synthesized in our lab and a monoclonal antibody to the C-terminal end of apo B-1OO of which the N-terminal 2152 amino acids are identical were used to examine the localization of these two apoliproteins in human tissues, The main aims of this study were, i) to demonstrate the specificity of the antibodies by investigating human ileum and liver, and ii) to determine whether there was evidence for the direct involvement of CMR in the formation of atherosclerosis plaque in humans. The endogeneous peroxidase activity in the tissue section were blocked and then microwaved to allow access of antibodies to the cell contents. Next, the slides were added with pig serum to block non-specific binding followed by incubating with appropriate antibodies. The bound antibodies were detected with an anti-species antiserum and the signal was enhanced by use of an avidin-biotin-peroxidase complex, which was visualized with diaminobenzidine in the presence of hydrogen peroxide.Apo B-8 was clearly visualized in the sections of ileum whereas apo B-100 was apparently absent from these same cells. These results were as expected and indicate that no, or very little, apo B-100 is formed in enterocytes. Hepatocytes were strongly stained for the presence ofapo B-100 and there was also a low level of staining for apo B-48, Since liver is the site of synthesis of apo B-100 and the lissues where CMR are taken up these results were also as expected.Sections of atherosclerotic plaques of aorta and heart tissue were also examined as were some 'fatty streak', The results showed that apo B-48 and apo B-100 were present in the aorta and heart tissue but not in fatty streak. These results indicate that CMR may contribute directly to the formation of atherosclerotic plaque of aorta and heart tissue via unknown mechanism.